(untitled) (Journal of Universal Science Research, 2024)
This article describes the formation of students’ moral maturity in the information environment. The spiritual maturity of the person, the requirements for the development of the spiritual maturity of students, the development indicators of media competence of university students, media psychology and its main tasks are given. Certain recommendations have been given for the formation of the skills of spiritual maturity in the formation of the competence of students to use information correctly.